Factors causing the gender pay gap - Ghasemi, Bardia (2022)
The research at hand aims to provide a comprehensive perspective on the factors causing the gender pay gap in European Union, especially in hierarchical organisational structures. Moreover, the study includes the identification of the factors and the consequences that they cause in the total wage distribution structure. Additionally, it provides top management with possible solutions regarding this issue and how to tackle the challenges in different stages of employees' career cycle from recruitment to promotion.